Human-centered design of e-health technologies concepts, methods and applications - Ziefle, Martina Cornelia 1962-; Röcker, Carsten 1975- (Medical Information Science Reference, 2011)
Unites researchers and industry practitioners from different disciplines to share their domain-specific knowledge and contribute to a holistic introduction into the area of human-centered design for e-health applications
Includes bibliographical references
Keywords: Medical informatics; Human-computer interaction; Human engineering; E-Health; Medizinische Informatik; Gesundheitswesen; Medizintechnik; Aufsatzsammlung